Transition experiences following involvement in an elite athlete residential program - Burden, S. A. (2002)
The aims of this thesis were to determine the relationship between transition model variables and athlete reactions to the transition event, the incidence of positive versus negative reactions to the event, identifications of variables that assisted or hindered the adaptation process, and the usefulness of the revised model for investigating a transition event. The study was conducted using a sample of adolescent athletes who participated in the residential program at the Australian Institute of Sport during the years 1993 to 1997. The findings highlighted areas for future consideration in research and development of transition programs for institutional settings.